Quality of aggregates for the preparation of asphalt mixtures from 4 processing companies in San José de Cúcuta, Colombia (2019)
Four asphalt mix processing companies were visited: Transivic S.A.S, Maquinteligente S.A.S, Copavicol S.A.S and Grupo Colpao S.A.S, companies located in the city of San José de Cúcuta, Colombia. Samples were taken of the stone material marketed by each of the companies for the preparation of asphalt mixtures, especially hot dense mixture-19. The stone aggregates taken from the processing companies were submitted to the analyses described by the "Instituto Nacional de Vías" 2013 for approval in the preparation of asphalt mixtures, regulations that apply in Colombia. The results obtained in the tests carried out with natural stone material were tabulated and analyzed comparatively in order to determine which of them is the most suitable for use in the preparation of the hot dense mixture-19. This provided interesting data on the quality of this material for the preparation of asphalt mixtures in each of the 4 processing companies. With the analysis of the results carried out, it was concluded that only 1 of the 4 material processing companies have high quality indexes. Research conclusion that provides information of interest to civil engineering contractors specialized in the construction of asphalt pavements, who will make important decisions regarding the acquisition of the ideal material for their next projects, thus constructing more durable works, a characteristic that contributes considerably to the economy of the project. In addition, a positive social and environmental impact is generated with the minimization of maintenance and repairs of the work carried out, an activity that leads to a reduction in the industrialized processes that generate polluting waste with respect to the preparation of construction materials for this type of projects.